Fractal space-time and variations of the hubble constant - Rozgacheva, Irina (Annals of Mathematics and Physics, 2023)
Spatial variations of the Hubble constant are considered according to Riess, et al. (2018). It is noted that the values of the Hubble constant form an almost fractal manifold. This fact suggests that the variations may be associated with local gravitational perturbations in the neighborhoods of galaxies, in which there are Cepheids and supernovae selected for measurement. The aim and purpose of the study is to show that the spatial variations of the Hubble constant may be due to the fact that the galaxies belong to outskirts of the Local Supercluster.